Antiprotozoal Screening of 60 South African Plants, and the Identification of the Antitrypanosomal Germacranolides Schkuhrin I and II - Mokoka, Tsholofelo A.; Xolani, Peter. K.; Zimmermann, Stefanie; Hata, Yoshie; Adams, Michael; Kaiser, Marcel; Moodley, Nivan; Maharaj, Vinesh; Koorbanally, Neil A.; Hamburger, Matthias; Brun, Reto; Fouche, Gerda (Planta Medica, 2013)
Two hundred and seven extracts were prepared from sixty plants from South Africa and screened for in vitro activity against Trypanosoma brucei rhodesiense, Trypanosoma cruzi, Leishmania donovani, and Plasmodium falciparum. For the 21 extracts which inhibited the growth of one or more parasites with more than 95 % at 10 µg/mL, the IC50 values against all four protozoal parasites and cytotoxic IC50 values against L6 myoblasts were determined. Amongst the most notable results are the activities of Psoralea pinnata (IC50 of 0.15 µg/mL), Schkuhria pinnata (2.04 µg/mL), and Vernonia mespilifolia (1.01 µg/mL) against Trypansoma brucei rhodesiense. HPLC-based activity profiling was used to identify the active constituents in the extracts, and the germacranolide sesquiterpene lactones schkuhrin I and II from S. pinnata, and cynaropicrin from V. mespilifolia were identified, with IC50 values of 0.9, 1.5, and 0.23 µM, respectively.
Keywords: screening; plant extract library; antiprotozoal activity; sesquiterpene lactones; Trypansoma brucei rhodesiense; Trypanosoma cruzi; Leishmania donovani; Plasmodium falciparum; Psoralea pinnata (Fabaceae); Schkuhria pinnata (Asteraceae); Vernonia mespilifolia (Asteraceae)